Inventory of Medicinal Plants that have the Potential to Treat Diabetes Mellitus in Sijunjung District - Mardiana Ikhwan; Syamsurizal; Des M.; Moralita Chatri (Jurnal Serambi Biologi, 2021)
Diabetes mellitus is a condition in which the pancreas no longer produces insulin properly, and results in an increase in glucose in the blood. Treatment using synthetic drugs is expensive, therefore some people use plants as medicine. One of them is the people of Sijunjung District, in this area traditional medicine is used to treat diabetes mellitus. This research was conducted from April to June 2021 using direct enumeration and interviews. Data was collected by means of in-depth interviews with key informants, namely traditional healers in every village and people who suffer from diabetes mellitus. The results showed that 43 types of plants belonging to 32 families have the potential as drugs for diabetes mellitus. The families that are often used as diabetes mellitus drugs by the people of Sijunjung District are the Asteraceae and Lamiaceae families. The plant organ that is most often used as a medicine for diabetes mellitus is the leaf. The way of processing the plant organs is boiled, pounded, squeezed, roasted and dried. How to use plants there are eaten and drunk. Most of the status of medicinal plants used are cultivated plants.